SUFISM IS A FORCE THAT LEADS MAN TO PERFECTION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The subject of this article is Sufism as a spiritual and moral doctrine. The aim of the study is to explore the role of Sufism in the formation of a perfect human being. The article briefly examines Sufi views on soul and body health, the education of the ideal person, and the teachings of thinkers as reflected in the works of Sufi figures. The analysis shows that Sufism offers a comprehensive system of spiritual self-improvement. The findings can be applied in the fields of religious studies, philosophy, and the psychology of personal development.
Keywords: Sufism, perfect man, soul, soul, Ahmed Yassawi, Bahauddin Naqshband, Najmuddin Kubro, Khoja Akhror, Nasafi.